(3MSf GdJhSd Edi UfGYI GdJQSds - (3GdTgGH eMehO , eMehO Hf SdeGf Hf agO Hf eMehO GdMfHdj GdMdHjGdOeTbj, CHhGdSfGA,J (B725 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg LGYd GdEfSGf eNHhAG JMJ GddSGf aEfg deG LYd Gddg dj aj cJGHI GdEfTGA QRbG HGTQJ HSHHg ef hXGFagG eG HGTQJ, hYGTQJ ef CLdg ef CcGHQ CgdgG hCFeJgG ef YGTQJ hQCjJ ef ePGgHge s
(3BNQgG (B:s
(3eHJhQ, hBNQ GdehLhO ajgG(B: (3hjchf Chd eG jdL eSGeYg UhJ ehdGfG eMeO QHg GdRjGOI aj NOeg hJcKjQ ef jVQH Hjf jOjg aj GdMQH HSjag, hjba aj GdSde CeGeg s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B167s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B259 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B666s
(3eUOQ GbJfGA GdCUd (B:s
(3EeHQhRjGfG (B(118) s
Keywords: (3GdCOHs